Campilobacteriosis as an important food toxiconinfection - Пінчук, Н. Г.; Пустовіт, Н. А. (Scientific Progress & Innovations, 2018)
Nutrition toxiconinfection is a wide group of acute intestinal infections that develop after eating foods infected with pathogens or opportunistic microorganisms. Clinically these diseases are characterized by sudden onset, the combination of intoxication syndromes, gastroenteritis and dehydration. Food-borne toxiconinfection occurs everywhere, which is due to the widespread spread of these pathogens in the environment. The highest morbidity is observed in economically developed countries of the world. In the general structure, acute intestinal infections occupy a dominant position, but their statistical record is imperfect. Therefore, it is not possible to fully assess the distribution of this group of diseases in the environment. Campylobacteriosis is one of the most urgent problems of food hygiene. This task is dictated by the necessity of incorporating microbiological research into the GKI prevention system, as well as the monitoring of pathogenic microorganisms in food products. In the developed world, the peak of the incidence of Smylobacter jejuni occurs in childhood, but it can also be seen in a larger adult age. Campylobacteriosis is characterized by polymorphism of clinical manifestations of infection. The most common form of infection is enterocolitis. Systemic lesions may also occur (septicemia, meningitis, cardiovascular disorders such as: thrombophlebitis, myocarditis, endocarditis, kidney and urinary tract, liver and gallbladder, nervous system: paresis, paralysis, polyneuritis, musculoskeletal system: arthritis, synovitis, bursitis) and neonatal pathology (septic abortions and preterm labor, accompanied by the development of septicemia, meningitis and enteritis in newborns). In humans, Campylobacteria come in more often with contaminated food products of animal origin. Water and food contamination with bacteria of the genus Campylobacter, direct contact with infected animals, it all can be the cause of the outbreak of acute intestinal infections.